2017
DOI: 10.1186/s12885-017-3713-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ADH1B and ALDH2 genes associated with the increased risk of gastric cancer in West Bengal, India

Abstract: BackgroundGastric cancer (GC) is one of the most frequently diagnosed digestive tract cancers and carries a high risk of mortality. Acetaldehyde (AA), a carcinogenic intermediate of ethanol metabolism contributes to the risk of GC. The accumulation of AA largely depends on the activity of the major metabolic enzymes, alcohol dehydrogenase and aldehyde dehydrogenase encoded by the ADH (ADH1 gene cluster: ADH1A, ADH1B and ADH1C) and ALDH2 genes, respectively. This study aimed to evaluate the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
3
17
1
4
Order By: Relevance
“…Analyses of liver, pancreas and colon cancer were presented due to evidence that these are alcohol-related cancers (21). Stomach cancer is presented due to previous investigations into its association with rs229984 (22)(23)(24)(25). Lung cancer is presented due to adequate sample size and significant findings.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of liver, pancreas and colon cancer were presented due to evidence that these are alcohol-related cancers (21). Stomach cancer is presented due to previous investigations into its association with rs229984 (22)(23)(24)(25). Lung cancer is presented due to adequate sample size and significant findings.…”
Section: Discussionmentioning
confidence: 99%
“…The transformation of ethanol into its carcinogenic metabolite, acetaldehyde, is especially important for the elimination of ADH1 in the liver [ 10 ]. A significant association was found between gastric cancer risk and a common 3′-untranslated region flanking a single-nucleotide polymorphism near rs1230025 of ADH1A [ 11 ]. The most important function-associated polymorphism in ADH is considered to be ADH1B Arg48His (rs1229984) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most important function-associated polymorphism in ADH is considered to be ADH1B Arg48His (rs1229984) [ 12 ]. Rs17033 of ADH1B is related to the risk of gastric cancer and smoking may further affect the role of rs671 [ 11 ]. Positive responses of ADH1B *3 and alcohol dependence have been found in African and Native American populations [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, large numbers of investigations have reported that gene polymorphism of ADHs was correlated with cancer risk [17,18,[31][32][33]. Moreover, the activity of ADH isoenzymes was signi cantly higher in liver cancer tissues than in healthy tissues [34], suggested the diagnostic value of ADH for the patients with liver cancer.…”
Section: Discussionmentioning
confidence: 99%